Design and implementation of a foot pressure measurement (Eurasian Journal of Research, Development and Innovation, 2024)
Foot plantar pressure is the pressure field that acts between the foot and the support surface during everyday locomotor activities. Information derived from such pressure measures is important in gait and posture research for diagnosing lower limb problems, footwear design, sport biomechanics, injury prevention and other applications. This work explain the way and the main component that used to design a system for measuring foot pressure. This system is characterized by simplicity and portability. So, it suitable for patient and economically viable in countries with people having low socioeconomic status.